Phenolic content and antioxidant activity of methanolic extracts of different parts of Anisophyllea disticha - Abdul bari, Nurul Ashikin; Sahena, Ferdosh; Sarker, Md Zaidul Islam; Shahari, Rozilawati (2017)
Anisophyllea disticha is one of the species of genus Anisophyllea that are being used by the folklore in treating diarrhea, dysentery, jaundice, revitalizing the birth canal of women, relieving weariness and body aches as well as acting as anti-aging and body refreshment. Different parts of A. disticha were tested for total phenolic content and antioxidant activity in terms of DPPH radical scavenging activity and ferric reducing antioxidant power assay (FRAP). From the results, methanolic stem extract showed highest total phenolic content followed by root and leaf with mean value of 27.7 ± 4.1 mg GAE / g extract, 19.5 ± 0.9 mg GAE / g extract and 12.2 ± 1.8 g GAE / g extract, respectively. The sequence of plant parts for results obtained in DPPH radical scavenging activity and FRAP assay followed this trend; stem > root > leaf, which corroborate with the results obtained for total phenolic content. High positive correlation was found between total phenolic content and antioxidant activity, suggesting that phenolic compounds contribute to antioxidant power of plant extracts.